Relación entre diabetes mellitus y tuberculosis en pacientes diabéticos tipo 2 atendidos en un hospital público de Loreto año 2018-2022 - Velasquez Ramirez, Amet Brayan (2024)
The comorbidity of diabetes mellitus and tuberculosis is a binomial that merits a multidisciplinary study due to the impact it has on public and intranosocomial health in terms of its form of contagion and incidental diagnosis. Therefore, the objective of this study is to determine the relationship between factors associated with Tuberculosis in diabetic patients in a public hospital in Loreto from 2018 to 2022. For this, the study was developed as a non-experimental, observational, cross-sectional, retrospective descriptive, case-control type in a sample of 164 patients with 82 who presented TB/DM-2 comorbidity (cases) and 82 who only presented DM-2. (controls). The TB diagnosis and screening criteria given by the MINSA technical standard were applied. The inferential analysis of the study was with chi2 and a P value less than 0.05. Resulting in 55% being female, 69% from urban origin and 49% with secondary education. 55% of the TB/DM-2 cases were male, 45% were adults over 55 years of age, 79% were from urban origins and 55% had secondary education. Male sex and urban origin were significantly associated with comorbidity (P< 0.001). In 87.8% of the cases of comorbidity, glycosylated hemoglobin presented values greater than 7% and this association was statistically significant (P< 0.05). Concluding that the sociodemographic factors associated with TB/DM 2 comorbidity in diabetic patients were male sex and urban origin. The uncontrolled HbA1C level with values greater than 7% is associated with the comorbidity of TB/DM-2 2. Harmful habits of alcohol and tobacco consumption were associated with the comorbidity of TB/DM-2.